Photocatalytic degradation of methylene blue dye utilizing nano-Tio2 photocatalyst with montmorillonite: Characterization, process and kinetic studies - Ng, Wen Jia (Universiti Malaysia Perlis, 2011)
Access is limited to UniMAP community.